TaADF3, an Actin-Depolymerizing Factor, Negatively Modulates Wheat Resistance Against Puccinia striiformis - Tang, Chunlei; Deng, Lin; Chang, Dan; Chen, Shuntao; Wang, Xiaojie; Kang, Zhensheng (Frontiers in Plant Science, 2016)
The actin cytoskeleton has been implicated in plant defense against pathogenic fungi, oomycetes and bacteria. Actin depolymerizing factors (ADF) are stimulus responsive actin cytoskeleton modulators. However, there is limited evidence linking ADFs with plant defense against pathogens. In this study, we have isolated and functionally characterized a stress-responsive ADF gene (TaADF3) from wheat, which was detectable in all examined wheat tissues. TaADF3 is a three-copy gene located on chromosomes 5AL, 5BL and 5DL. A particle bombardment assay in onion epidermal cells revealed the cytoplasmic and nuclear localization of TaADF3. The expression of TaADF3 was inducible by abscisic acid (ABA), as well as various abiotic stresses (drought and cold) and virulent Puccinia striiformis f. sp. tritici (Pst) but was down regulated in response to avirulent Pst. Virus-induced silencing of TaADF3 copies enhanced wheat resistance to avirulent Pst, with decreased reactive oxygen species (ROS) accumulation and hypersensitive response (HR). Upon treatment with virulent Pst, TaADF3-knockdown plants exhibited reduced susceptibility, which was accompanied by increased ROS production and HR. Interestingly, the silencing of TaADF3 resulted in hindered pathogen penetration and haustoria formation for both avirulent and virulent Pst. Moreover, the array and distribution of actin filaments was transformed in TaADF3-knockdown epidermal cells, which possibly facilitated attenuating the fungus penetration. Thus, our findings suggest that TaADF3 positively regulates wheat tolerance to abiotic stresses and negatively regulates wheat resistance to Pst in an ROS-dependent manner, possibly underlying the mechanism of impeding fungal penetration dependent on the actin architecture dynamics.